2021
DOI: 10.3390/fi14010001
|View full text |Cite
|
Sign up to set email alerts
|

Query Processing in Blockchain Systems: Current State and Future Challenges

Abstract: When, in 2008, Satoshi Nakamoto envisioned the first distributed database management system that relied on cryptographically secured chain of blocks to store data in an immutable and tamper-resistant manner, his primary use case was the introduction of a digital currency. Owing to this use case, the blockchain system was geared towards efficient storage of data, whereas the processing of complex queries, such as provenance analyses of data history, is out of focus. The increasing use of Internet of Things tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 124 publications
0
9
0
Order By: Relevance
“…The system also promised that trust can be earned by rewarding "miners" (nodes that verify the validity of a transaction and append valid blocks to the rest of the chain) with token incentives [24]. Such cryptographic validation processes require massive computational power and therefore make it logically insensible for a malevolent block to validate a faulty record and maintain the faulty version of the truth throughout the entirety of the chain [25].…”
Section: Background Concepts For Blockchain Technologymentioning
confidence: 99%
“…The system also promised that trust can be earned by rewarding "miners" (nodes that verify the validity of a transaction and append valid blocks to the rest of the chain) with token incentives [24]. Such cryptographic validation processes require massive computational power and therefore make it logically insensible for a malevolent block to validate a faulty record and maintain the faulty version of the truth throughout the entirety of the chain [25].…”
Section: Background Concepts For Blockchain Technologymentioning
confidence: 99%
“…Lightweight blockchain also uses a combination of cryptographic techniques and optimization strategies. In a lightweight blockchain, query processing is conducted by the network nodes responsible for verifying transactions and maintaining the blockchain [46]. The information saved in a block is merely the Merkle root information, as explained in Fig.…”
Section: High-performance Data Structures For Multi-query Processing ...mentioning
confidence: 99%
“…Some examples of applications are: (1) Detecting accounts used by the same user; (2) Detecting account behaviours; (3) Account clustering; (4) Wealth movements; and others. Some surveys about blockchain technology have already identified that the problem of a missing unified model exists [Przytarski et al 2021, Huang et al 2021]. However, no study has been found regarding a unified data model for blockchain data; and no study about the entities and the attributes that compose most blockchain networks.…”
Section: Context and Motivationmentioning
confidence: 99%